Tuberculosis Treatment Outcomes and Associated Factors among TB Patients Attending Public Hospitals in Harar Town, Eastern Ethiopia: A Five-Year Retrospective Study - Tola, Assefa (Tuberc Res Treat, 2019)
INTRODUCTION: Tuberculosis remains a major public health threat throughout the world particularly in developing countries. Evaluating the treatment outcome of tuberculosis and identifying the associated factors should be an integral part of tuberculosis treatment. OBJECTIVES: The aim of this study was to assess the treatment outcome of tuberculosis and its associated factors among TB patients in the TB clinics of Harar public hospitals, Eastern Ethiopia, 2017. METHODS: A retrospective document review was conducted in two public hospitals of Harar town, located 516 km east of Addis Ababa. A systematic random sampling technique was used to select the document of TB patients who were registered in the hospitals from 1st of January, 2011, to 30th of December, 2015. The data were collected using a pretested structured data extraction format. SPSS Version 21 for window was used for data processing. Bivariate and multivariate analysis with 95% confidence interval was employed in order to infer the associations between TB treatment outcome and potential predictor variables. RESULTS: One thousand two hundred thirty-six registered TB patients' documents were reviewed. Of these, 59.8% were male, 94.2% were urban dwellers, 97% were new cases, 61.2% were presented with pulmonary TB, and 22.8% were HIV positive. Regarding the treatment outcome, 30.4% were cured, 62.1% completed their treatment, 3.9% died, 2.4% were defaulted, and the remaining 1.2% had failed treatment. The overall rate of the treatment success among the patients was 92.5%. In the present study, being female (AOR = 1.89, 95% CI: 1.14 - 3.14), having pretreatment weight of 20 – 29 kg (AOR = 11.03, 95% CI: 1.66 - 73.35), being HIV negative (AOR = 6.50, 95% CI: 3.95 - 10.71), and being new TB patient (AOR = 3.22 95% CI: 1.10 - 9.47) were factors independently associated with successful treatment outcome. On the other hand, being in the age group 54 – 64 years (AOR =10.41, 95% CI: 1.86 - 58.30) and age greater than 65 years (AOR =24.41, 95% CI: 4.19 - 142.33) was associated with unsuccessful TB treatment outcome. CONCLUSION: In the current study, the rate of successful TB treatment outcome was acceptable. This rate should be maintained and further improved by designing appropriate monitoring strategies.